Crime news and ethics in Serbian press 100 years ago and today: An analysis of the content of the newspapers "Pravda", "Vreme" and "Politika" from February 1st to 29th, 1924, and the newspapers "Kurir", "Večernje novosti" and "Politika" from February 1st to 29th, 2024 - Cvejić, Bojan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The public's attention in crime news and headlines about accidents and tragedies is not a trend of the new age. News from the so-called "crime chronicle" has been published in the media since the beginning of journalism. Although there is often no public interest in them, but rather a predominance of public curiosity, "black news" has always found its way to the audience through the media. Nowadays, especially in the media in Serbia, examples from this thematic area are most commonly cases in which journalists cross professional boundaries and violate ethical standards. Based on experience and practice in recent decades, numerous rules regarding reporting on criminal acts and personalities, who are direct or indirect actors in such events, have been established through media ethical codes and competent laws. The aim of this research is to establish what has changed in the Serbian media in this regard compared to a hundred years ago, when ethical codes were in their early stages without guidelines and precise rules.
Keywords: media, journalism, news, newspaper, crime, media ethics, ethics